2011
DOI: 10.1007/s00277-011-1384-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of human leukocyte antigens as predisposing and/or protective factors in patients with idiopathic thrombotic thrombocytopenic purpura

Abstract: Fifty-four adult German patients suffering from idiopathic thrombotic thrombocytopenic purpura (TTP) have been examined for HLA class II. All patients presented autoantibodies against ADAMTS13 and ADAMTS13 activity levels <5%. Blood samples have been analyzed for HLA-DRB1 and DQB1 alleles using sequence-specific primer PCR and sequence-specific oligonucleotide PCR. Reference data of German bone marrow and blood donors were obtained from www.allelefrequencies.net. The results were evaluated employing two-sided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 17 publications
2
52
3
Order By: Relevance
“…Together with previous reports, our findings suggest that, HLA-DRB1*11 is related to syndromes of thrombotic microangiopathy, including TTP, [22][23][24] haemolytic uraemic syndrome 33 and TA-TMA. The observed association of HLA-DRB1*11 and TA-TMA indicate that the role of HLA-DRB1*11 in the pathogenesis of thrombotic microangiopathies might be complex and extend beyond susceptibility to autoantibody formation against ADAMTS13.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Together with previous reports, our findings suggest that, HLA-DRB1*11 is related to syndromes of thrombotic microangiopathy, including TTP, [22][23][24] haemolytic uraemic syndrome 33 and TA-TMA. The observed association of HLA-DRB1*11 and TA-TMA indicate that the role of HLA-DRB1*11 in the pathogenesis of thrombotic microangiopathies might be complex and extend beyond susceptibility to autoantibody formation against ADAMTS13.…”
Section: Discussionsupporting
confidence: 87%
“…In recent years, an association of HLA-DRB1*11 and idiopathic TTP has been recognised by independent groups. [22][23][24] Our hypothesis was that in view of the correlations between the two conditions, HLA-DRB1*11 might have a role in the pathogenesis of TA-TMA, as well.…”
Section: Introductionmentioning
confidence: 99%
“…Three independent studies have shown that HLA-DRB1*11 is a risk factor for acquired TTP, which further implicates CD4 1 T cells in the pathogenesis of this disease. [13][14][15] We have previously shown that ADAMTS13 is endocytosed by antigen-presenting cells such as dendritic cells (DCs) by the macrophage mannose receptor (MMR). 16 After its intracellular processing, a restricted set of ADAMTS13-derived peptides is presented on major histocompatibility complex class II for presentation to CD4…”
mentioning
confidence: 99%
“…It has been observed that the HLA-DRB1*11 is more frequent in patients with acquired TTP when compared with a control population. [29][30][31] These findings indicate that presentation of ADAMTS13-derived peptides on MHC II molecules by APC is necessary to activate ADAMTS13-specific CD41 T cells. We have recently shown that ADAMTS13 is efficiently internalized by immature dendritic cells (iDCs) through the macrophage mannose receptor.…”
Section: Introductionmentioning
confidence: 84%
“…Four of the donors were heterozygous for DRB1*11, which was recently identified as a risk factor for the development of acquired TTP (Table 1). [29][30][31] DCs derived from 4 DRB1*11-negative donors are also included ( Table 1). The total number of HLA-DR-presented peptides meeting our criteria ranged between 100 and 360 unique presented peptides (supplemental Figure 1A).…”
Section: Analysis Of Adamts13-presented Peptides On Mhc Class II Molementioning
confidence: 99%